Developing synthetic biology tools for acetogens - Redfern, Elizabeth (2022)
Acetogenic bacteria are of industrial interest due to their capacity for autotrophic growth on single carbon (C1) feedstocks such as CO or CO2 and H2. Both Eubacterium limosum and Clostridium carboxidivorans can autotrophically produce four carbon (C4) products, with C. carboxidivorans also able to produce six carbon (C6) products, such as hexanol and hexanoate. E. limosum is also capable of autotrophic growth on methanol. This study outlines efforts to further the industrial potential of these strains through the development of DNA transfer methods, synthetic biology toolkits and a large transposon mutant library elucidating gene essentiality under industrially relevant conditions.